(untitled) (Biological Sciences - PJSIR, 2001)
The percentage yield and chemical composition of fixed oil of Citrus sinensis varieties Valencia and Salustiana have been studied. The percentage yield of fi xed oils from t he seeds of these two var i eties were 40.0 I and 36.66% respecti vel y. The percentage fatty acids com position of the respecti ve oils were characterised as C12 ( 1 .55, 0.0 ), C ,( 5.04 , 0 0), C , ( 47 .33, 29 . 1 3), C J 7.50, 4.23) , C,s/ 1 8.40, 26.03) ,C, ,(l 8.39, 37 .51) and C, /0.0, 3.07) 1 1 18 8 8 respecti vel y. This chemical composition suggests that the oils, when a vailable i n quan tity can fi nd appl ication both for edible or soap maki ng purposes.